THE EFFECTIVENESS OF DIGITAL MEDIA-ASSISTED RECIPROCAL TEACHING ON ELEMENTARY STUDENTS’ READING COMPREHENSION SKILLS - Laily, Idah Faridah; Setiawan, Dadan; Arifuddin, Ahmad (PD PGMI se Indonesia, 2025)
Traditional instructional methods often fail to develop students' metacognitive and evaluative reading skills, necessitating innovative pedagogical approaches that leverage digital technology to enhance literacy development. This study aimed to evaluate the effectiveness of a digital media-assisted reciprocal learning strategy on fifth-grade elementary students' reading comprehension skills. This study used a quantitative approach with a quasi-experimental method. The study participants consisted of 302 grade V students (aged 10-11 years) from six elementary schools in urban Indonesia. The intervention was conducted over one semester. Data were collected through a Reading Comprehension Test of 30 questions and classroom observations. The analysis included descriptive statistics and ANCOVA to test the main hypothesis. The experimental group showed a significant increase in reading comprehension compared to the control group, sig=0.001<0.05 (Cohen's d = 1.34). The increase was especially seen in the dimensions of metacognitive awareness (Cohen's d = 1.37) and evaluative reading (Cohen's d = 1.32), indicating that the integration of digital media with reciprocal learning strategies effectively improved high-level comprehension skills. Conclusion: Reciprocal learning with the assistance of digital media is an effective approach to improving students' reading comprehension skills. This research has contributed to the utilization of digital technology with reciprocal learning strategies effectively in literacy learning.